Oblicz krok po kroku:
[tex]\frac{1}{8}-\frac{3}{4}:(-\frac{11}{6}+\frac{30}{6})[/tex]


Odpowiedź :

[tex]\frac18-\frac34:(-\frac{11}6+\frac{30}6)=\\\frac18-\frac34:\frac{19}6=\\\frac18-\frac34*\frac6{19}=\\\frac18-\frac3{2}*\frac3{19}=\\\frac18-\frac9{38}=\\\frac{19}{152}-\frac{36}{152}=\\-\frac{17}{152}[/tex]

Odpowiedź:

Szczegółowe wyjaśnienie:

[tex]\frac{1}{8} - \frac{3}{4} : \left(-\frac{11}{6} + \frac{30}{6} \right) = \\\\ \frac{1}{8} -\frac{3}{4} : \frac{19}{6} = \\\\ \frac{1}{8} - \frac{3}{4} \cdot \frac{6}{19} = \\\\ \frac{1}{8} - \frac{9}{38} = \\\\ \frac{19}{152} - \frac{36}{152} = -\frac{17}{152}[/tex]

Kolejność wykonywania działań

1 nawiasy  

2 dzielenie  

3 mnożenie  

4 odejmowanie  

5 dodawanie  

Zobacz obrazek Jezowj